Cegah Kekerasan Seksual: Pembinaan Emosional dan Spiritual melalui Pelatihan ESQ bagi Remaja I-Generation - Muhamad Taufik BK; Lilis Karyawati; Nunung Kurniasih (Al-Qalam Institute, 2022)
The purpose of this community service is to increase theinsight and skills of the santri (i-generation) in managingemotions and spirituality to prevent and overcome rampantsexual violence among santri. The methods used are training,quizzes, games, and fun learning. The results show that thestudents appear to have increased knowledge about acts ofsexual violence. Apart from that, through ESQ training, thestudents as the i-generation have the skills in managingemotional and spiritual matters to control themselves fromfalling into acts of sexual violence that are denounced byreligion. Santri can also identify the characteristics of actionsthat lead to sexual violence and have the knowledge andskills to prevent or avoid it and find appropriate solutions.The partners recommend that on other occasions, trainingcan be carried out that leads to entrepreneurial skills thathave economic value and profits that are useful for theprogress of students and Islamic boarding schools.